Conchostráceos com linhas de crescimento recurvadas junto à margem dorsal (Famílias Palaeolimnadiopseidae e Perilimnadiidae) da Formação Rio do Rasto, permiano superior, Bacia do Paraná, Brasil - Ferreira-Oliveira, Luis Gustavo [UNESP]; Rohn, Rosemarie [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2008)
Some Upper Permian conchostracans from the Rio do Rasto Formation (Paraná Basin, South Brazil) have very characteristic recurved growth lines at the dorsal margin. All previously described specimens were classified as Palaeolimnadiopsis subalata (Reed) Raymond. However, a re-analysis of these fossils and of additional recently- collected specimens demonstrated that not all can be included in a single species, nor only in the Family Palaeolimnadiopseidae. According to their shape and the size of the umbo, they are classified into three species. The sub-elliptic carapaces with small anterior umbo are maintained in Palaeolimnadiopsis subalata (Reed, 1929) Raymond, 1946. The sub-circular carapaces with small sub-central umbo correspond to the new species Palaeolimnadiopsis riorastensis. The small size of the umbo is a character of the Family Palaeolimnadiopseidae. The small elliptic valves with large anterior umbo are assigned to the new species Falsisca brasiliensis of the Family Perilimnadiidae, which is characterized by large umbos. Palaeolimnadiopsis has a wide chronostratigraphic distribution, but Falsisca is restricted to the Upper Permian-Lower Triassic of Europe and Asia. This interval is in agreement with the probable Late Permian age of the respective strata of the Rio do Rasto Formation. Falsisca was not previously recorded in Gondwana.
Conchostracans with recurved growth lines at the dorsal margin (Family Palaeolimnadiopseidae and Perilimnadiidae) from the Rio do Rasto Formation, Upper Permian, Parana Basin, Brazil
Keywords: Conchostraca; Palaeolimnadiopseidae; Paraná Bbasin; Perilimnadiidae; Upper Permian; bivalve; chronostratigraphy; fossil; growth; morphology; new species; Permian; Triassic; Parana Basin; South America; Falsisca